Easy western blot solution - Heo, Yub (Nanyang Technological University, 2022)
The Western Blot protocol is a widely used life science technique developed in the 1970s to detect the presence of a specific protein in a given sample. It is commonly used in areas such as disease detection in clinical settings, amongst other biochemistry applications. However, the technique is time consuming when performed manually, taking up to two days to complete. Furthermore, attempts to automate the process are relatively new and have low adoption rates due to the prohibitive cost of the device and consumables. This presents an opportunity for a low-cost device to automate the Western Blot.